2019
DOI: 10.3329/jbau.v17i2.41972
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin attenuates butter fat induced hyperlipidemia in mice

Abstract: Long-term intake of high-fat food disrupts lipid metabolism, resulting in fat accumulation, obesity, and hyperlipidemia. Curcumin, active ingredients of turmeric plants, has been shown to possess potent antioxidant and hypolipidemic properties. The study was conducted to observe the effects of curcumin on butter induced hyperlipidemia, hematological values and physio-pathological alterations in liver and aorta in mice. A total of 40 Swiss Albino mice (Mus musculus), aged 28-30 days with an average body weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
(17 reference statements)
1
7
0
Order By: Relevance
“…Blood samples were collected directly from heart (Sarker et al, 2019). The mice were kept fasting overnight.…”
Section: Blood Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood samples were collected directly from heart (Sarker et al, 2019). The mice were kept fasting overnight.…”
Section: Blood Sample Collectionmentioning
confidence: 99%
“…The serum biochemical profile like total serum cholesterol, triglycerides (TG), high density lipoprotein (HDL cholesterol), low density lipoprotein (LDL cholesterol), alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), creatinine and glucose were performed at Professor Dr. Mohammad Hussain Central Laboratory in Bangladesh Agricultural University, Mymensingh-2200 colorimetrically using Humalyzer 2000 (Human type, Germany) following instructions provided by Sarker et al, 2019.…”
Section: Serum Biochemical Studiesmentioning
confidence: 99%
“…Curcumin, 7-bis-(4-hydroxy-3-methoxyphenyl)-1,6-heptadiene-2,5-dione, is a yellow-orange polyphenol compound derived from the rhizome of Curcuma longa L. , which has been commonly used as a spice and natural coloring agent for a long time [ 5 ] and a natural additive for food and cosmetics recognized by the WHO and Food and Drug Adminstration (FDA). Also, curcumin has been successfully exploited as a traditional medicine in China and India due to its diverse biological and pharmacological activities, such as lowering blood lipids [ 6 ], anti-tumor [ 7 ], anti-inflammatory [ 8 ], antioxidant [ 9 ], anti-hepatotoxicity [ 10 ], and anti-bacterial properties [ 11 ], which has aroused widespread attention by scholars because of the application of curcumin in pharmacology and clinical medicine. However, it has been reported that excess curcumin will cause DNA inactivation, lead to a decrease in intracellular ATP levels, and trigger the tissue necrosis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperlipidemia is a metabolic disorder that results from an impaired lipid metabolism indicated by an elevated level of plasma lipids in the blood 1 . Hyperlipidemia has been acknowledged as a risk factor for atherosclerotic cardiovascular disease (ASCVD), coronary heart disease (CHD), transient ischemic attack (TIA), and ischemic heart disease (IHD).…”
Section: Introductionmentioning
confidence: 99%